Persepsi Siswa terhadap Penggunaan Media Flashcard dalam Pembelajaran Bahasa Inggris di SDN 1 Gili Indah: Penelitian - Elthia, Memy Wardani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe students' perceptions of the use of flashcards in English learning at SDN 1 Gili Indah. Flashcards, as a visual medium, are considered to help students understand and remember vocabulary more effectively through an engaging combination of images and words. The research approach used a qualitative descriptive method, involving fifth and sixth grade students as respondents. Data were collected through observation, interviews, and questionnaires. The results showed that most students had positive perceptions of the use of flashcards. Students felt more motivated, easily understood vocabulary, and were more active in participating in the learning process. Furthermore, the use of flashcards was also proven to create a fun and interactive learning atmosphere. These findings indicate that flashcards are an effective learning medium for improving English vocabulary mastery in elementary school students, particularly at SDN 1 Gili Indah. This study recommends that teachers continue to utilize visual media such as flashcards to improve the quality and outcomes of student learning.